Synergistic Anti-inflammatory Activity of Tinospora crispa L. and Zingiber officinale: A BSA Assay Study - Dewi, Sari Puspita; Kurnia, Achdi; Permata Sari, Shinta Dewi; Budiman, Muhamad Arif (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2025)
Ginger rhizome (Zingiber officinale) and Tinospora crispa L. (Tinospora crispa L.) extracts contain various active compounds that have the potential to be anti-inflammatory agents. This study aims to evaluate the anti-inflammatory activity of ginger rhizome and Tinospora crispa L. leaf extracts, both singly and in combination, using the BSA test method. Extraction was carried out using the maceration method with 70% ethanol solvent. Anti-inflammatory activity tests were carried out in vitro at 75, 100, and 150 μg/mL concentrations by measuring the extract's ability to prevent heat-induced BSA denaturation. The yield of Tinospora crispa L. extract reached 41.39% and that of ginger extract 25.63%. The combination of 150 μg/mL extracts showed the highest anti- inflammatory activity (96.82%) of all the extract test samples. In comparison, the lowest anti-inflammatory activity was found in 75 μg/mL ginger extract, at 89.21%. Statistical tests showed a significant difference between the 75 μg/mL ginger extract and the 150 μg/mL combination (p=0.047). The combination of ginger and Tinospora crispa extract has the potential to be developed as a natural anti-inflammatory agent.